Foreign experience of social education in the aspect of competence approach - КатаєвC. Л. (SOCIOPROSTIR: the Interdisciplinary Online Collection of Scientific Works on Sociology and Social Work, 2019)
The experience of social education in England based on the materials of the periodical “Social Education” magazine is discussed. It is noted that social education is understood as a set of types of practical training for schoolchildren to develop competence in various social situations of a person’s life, such as the protection of civil rights, interaction with law enforcement agencies and municipal organizations, communication in social networks. Attention is paid to the role of social education for the formation of various types of life competence.